Limb-salvage surgery versus extremity amputation for early-stage bone cancer in the extremities: a population-based study - Zhu, Yixu; Wu, Xuesong; Zhang, Wenjun; Zhang, Haijun (Frontiers in Surgery, 2023)
Background: Many attempts have been made to induce limb salvage as an alternative to amputation for primary bone cancer in the extremities, but efforts to establish its benefits over amputation yielded inconsistent results with regard to outcomes and functional recovery. This study aimed to investigate the prevalence and therapeutic efficiency of limb-salvage tumor resection in patients with primary bone cancer in the extremities, and to compare it with extremity amputation. Methods: Patients diagnosed with T1-T2/N0/M0 primary bone cancer in the extremities between 2004 and 2019 were retrospectively identified from the Surveillance, Epidemiology, and End Results program database. Cox regression models were used to test for statistical differences between overall survival (OS) and disease-specific survival (DSS). The cumulative mortality rates (CMRs) for non-cancer comorbidities were also estimated. The evidence level in this study was Level IV. Results: A total of 2,852 patients with primary bone cancer in the extremities were included in this study, among which 707 died during the study period. Of the patients, 72.6% and 20.4% underwent limb-salvage resection and extremity amputation, respectively. In patients with T1/T2-stage bone tumors in the extremities, limb-salvage resection was associated with significantly better OS and DSS than extremity amputation (OS: adjusted HR, 0.63; 95% confidence interval [CI], 0.55-0.77; p < 0.001; DSS: adjusted HR, 0.70; 95% CI, 0.58-0.84; p < 0.001). Limb-salvage resection was associated with significantly better OS and DSS than extremity amputation for patients with limb osteosarcoma (OS: adjusted HR, 0.69; 95% CI, 0.55-0.87; p = 0.001; DSS: adjusted HR, 0.73; 95% CI, 0.57-0.94; p = 0.01). Mortality from cardiovascular diseases and external injuries was remarkably declined in primary bone cancer in the extremities patients who underwent limb-salvage resection (cardiovascular diseases, p = 0.005; external injuries, p = 0.009). Conclusion: Limb-salvage resection exhibited excellent oncological superiority for T1/2-stage primary bone tumors in the extremities. We recommend that patients with resectable primary bone tumors in the extremities undergo limb-salvage surgery as the first choice of treatment.